Finding a Balance between Accuracy and Effort For Modeling Biomineralization. (November 2016) - Hommel, Johannes; Ebigbo, Anozie; Gerlach, Robin; Cunningham, Alfred B.; Helmig, Rainer; Class, Holger
Abstract: Microbially induced calcite precipitation (MICP) is a technology aiming at the mitigation of potential leakage from underground gas storage sites. A numerical model for MICP was previously developed and validated. The model complexity leads to high computation times, prohibiting at the moment the use of the model for designing field-scale MICP applications. This study investigates savings of the computational time by well-chosen model simplifications. Additionally, this approach is motivated by the high uncertainty of relevant input-parameters. Excessively detailed equations are unnecessary burdens to the MICP model, whose reliability is influenced by the input-parameter uncertainty.